Relationship between Culture and Self-Efficacy with Risk of Suicide among High School Adolescents in Langke Rembong District, Manggarai Regency, East Nusa Tenggara - Claudia Dewi; Fransiska Yuniati Demang (International Journal of Nursing and Health Services (IJNHS), 2021)
The changing times have resulted in a greater variety of problems that cause stress and the weaker one's ability to cope with stress. This results in higher cases of suicide and a higher risk of suicide. Assessment of the risk of suicide is important to pay attention to cultural factors other than individual factors. Various attempts have been made to reduce the suicide rate. One of the efforts that can be done to reduce suicide rates is to increase individual self-efficacy. This study aims to determine how the relationship between self-efficacy and culture is related to the risk of suicide in adolescents in Langke Rembong District, Manggarai Regency, East Nusa Tenggara Province. This study used a cross-sectional quantitative approach. The population in this study were adolescents in Manggarai Regency with a sample size of 274 people. Data collection was carried out using the Assessment of Suicidal Intention (ASI), Cultural Assessment of Risk for Suicide (CARS) General Self Efficacy Scale (GSES). The results showed a significant relationship between CARS and GSES with a p value of 0,000 and a significant relationship between ASI and GSES with a p value of 0.003.The results of the Manova test showed a significant relationship between self-efficacy and the risk of suicide using CARS and GSES. p value <0.05. Good self-efficacy can be a protective factor against suicide risk, vice versa, low self-efficacy can be a risk factor for suicide.